PENDAMPINGAN PENERAPAN BIMBINGAN PRIBADI DAN BIMBINGAN BELAJAR MATEMATIKA UNTUK MEMBANGUN RESILIENSI SISWA KELAS 6 SD CAHAYA BANGSA UTAMA - Setiawan, Yustinus Budi; Sumarah, Ignatia Esti (Jurnal Berdaya Mandiri, 2019)
ABSTRACTAt the beginning of academic year of 2018/2019, grade 6 students of Cahaya Bangsa Utama Elementary School were inclined to be saturated, bored, and troubled about drilling method for Final Exam preparation. They frequently grumbled when they were doing some tasks, especially math. This behavior inhibits student?s learning process and make them less resilient. Therefore, the purpose of the activities of Community Service is to guide vice principal of student affairs to conduct personal guidance program and math tutoring program (assisted by grade 6 teacher and math teacher.    Based on growth mindset theory,  personal guidance program facilitates the students to attain positive perception of math. They, accordingly, understand the benefit of math toward their life, both today and future days. Growth mindset theory also underlines that talents and skills are not predetermined at birth, but cultivated through efforts, shaperned and trained; therefore math tutoring may build students? resilience in doing math exercises.